Evaluation of hematological parameters in pulmonary tuberculosis patients - Amar R Shah; Killol N Desai; Alpeshkumar M Maru (Journal of Family Medicine and Primary Care, 2022)
Introduction: Tuberculosis (TB) is the most common infectious disease caused by mycobacterium tuberculosis. Apart from the lungs, tuberculosis also affects the bone marrow. There are significant hematological abnormalities that occur in association with tuberculosis. So we can use these hematological parameters as a marker for the diagnosis, prognosis, and response to therapy. Aims: To evaluate the hematological parameters in pulmonary tuberculosis patients. Methods and Materials: A total of 70 diagnosed tuberculosis patients and 70 healthy controls were selected by purposive sampling in this study. About 4 ml of venous blood was collected with proper aseptic precaution. 2 ml ethylenediamine tetra acetic acid (EDTA) tube blood was used for hematological analysis by using Siemens Advia 2120i 5-part hematology analyzer. Rest 2 ml blood was used for measurement of erythrocyte sedimentation rate (ESR) by Wintrobe's method. Results: The hemoglobin, packed cell volume (PCV), and blood indices values were significantly lower compared to healthy controls in both sexes. White blood cell (WBC) count, absolute neutrophil count, platelet count, and ESR values were significantly increased in tuberculosis patients as compared to healthy controls and were found to be statistically significant (P-value < 0.05). Conclusions: To measure hematological parameters in tuberculosis is a simple and cost-effective method to predict the course of the disease and monitor complications in developing countries like India.